Cinema and Poetry: a Theoretical Proposal (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The relationship between narrative and cinema is a natural result of their mutual dependence on fiction. In fact, a good percentage of films are based on literary works of narrative function, so much so that many awards, such as the Oscar, include a special category for adaptation of pre-existing literary material. The cinema we are talking about here is that of a narrative nature, not that of pure exposition of images or mere experimentation. The relationship between novel or story and cinema is marked by the structuring presence of argument, plot or intrigue in the composition of the works that make up these Arts. And it is necessary to highlight precisely this: that these are not different genres, but rather arts based on heterogeneous means of expression (note)